2016
DOI: 10.1111/eff.12321
|View full text |Cite
|
Sign up to set email alerts
|

Bioenergetic evaluation of diel vertical migration by bull trout (Salvelinus confluentus) in a thermally stratified reservoir

Abstract: Many species living in deeper lentic ecosystems exhibit daily movements that cycle through the water column, generally referred to as diel vertical migration (DVM). In this study, we applied bioenergetics modelling to evaluate growth as a hypothesis to explain DVM by bull trout (Salvelinus confluentus) in a thermally stratified reservoir (Ross Lake, WA, USA) during the peak of thermal stratification in July and August. Bioenergetics model parameters were derived from observed vertical distributions of temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Katinic, Patterson, & Ydenberg, ; Newell & Quinn, ). Yet, our observation that tagged females did not use the coolest temperatures available was consistent with previous studies that have shown fish to select intermediate temperatures in lakes (Armstrong et al., ; Eckmann, Dunham, Connor, & Welch, ). At low temperatures, sockeye salmon have reduced aerobic scope for oxygen‐dependent processes, such as swimming.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Katinic, Patterson, & Ydenberg, ; Newell & Quinn, ). Yet, our observation that tagged females did not use the coolest temperatures available was consistent with previous studies that have shown fish to select intermediate temperatures in lakes (Armstrong et al., ; Eckmann, Dunham, Connor, & Welch, ). At low temperatures, sockeye salmon have reduced aerobic scope for oxygen‐dependent processes, such as swimming.…”
Section: Discussionsupporting
confidence: 91%
“…tures in lakes (Armstrong et al, 2016;Eckmann, Dunham, Connor, & Welch, 2016). At low temperatures, sockeye salmon have reduced aerobic scope for oxygen-dependent processes, such as swimming.…”
Section: It Remains Unclear Whether Insufficient Time On Spawning Gromentioning
confidence: 99%
“…Previous research has shown that bull trout have strong behavioral and physiological responses to their habitat, including temperature and prey availability (Eckmann et al, 2018; Gutowsky et al, 2017; Selong et al, 2001). Our study complements these by exploring how movement patterns and associated temperatures can influence growth potential across a heterogeneous river–reservoir system.…”
Section: Discussionmentioning
confidence: 99%
“…Bull trout may shift among thermal heterogeneous locations for various reasons such as predator avoidance, prey availability, or maximum growth (Selong et al, 2001; Gutowsky et al, 2017; but see Howell et al, 2010). Recently hypothesized is that bull trout may occupy colder temperatures to improve gamete viability (Eckmann et al, 2018) or minimize metabolic costs (Armstrong & Bond, 2013). Temperature is an important driver in reproductive development and egg viability in female fish (Jobling, Johnsen, Pettersen, & Henderson, 1995; Rideout et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation